PENGARUH PEROLEHAN RITASE KENDARAAN TERHADAP PENDAPATAN SETIAP KENDARAAN ANGKUTAN BARANG: (Studi Kasus Pada Perusahaan Angkutan di Pandaan Pasuruan) - Indah Sari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2014)
Expedition company as the transportation company are have very important roles in goods flow chain from one place to the other places. In addition, with their capability and skill, the expedition service can organize of delivering implementation through land, sea, and air. Thus the expedition are offers more services for trading (transporting/acceptance) of the goods from the producer until to the consumers. One of the company that provides goods expedition services which operates in Pasuruan to fulfill the need of goods expedition services. The objectives of this research are to analyze whether the trips gaining of the vehicles that are supported by variables of loading and unloading process, distance of the good delivering, physical condition and traffic eftfae road, driver behavior, and vehicle condition are have significant effects on revenue of each freight vehicles. Population that used in this research are all of vehicles that existing in the company by amount of 50 vehicles. The methods of data analysis that used are validity, reliability and regression analysis test.